De skeletten uit het grafmonument te Rijnsburg: een hernieuwd onderzoek (Bulletin KNOB, 1998)
A renewed research of the remains of skeletons in the sepulchral monument at Rijnsburg, which were excavated in the years 1949/50 and were then ascribed to family members of the count of Holland, took place in the years 1995/96. A bone sample was taken from the left thighbone of each of the 16 skeletons for the purpose of 14C datings. The results show a 300 to 600 years' discrepancy with the supposed historical data. From the physiological-anthropological research it was concluded that the demographic and osteopathological findings are inconsistent with the historically known information to such a degree, that there is no ground for a positive identification with the members of the count's family of Holland buried at Rijnsburg.An extensive analysis of all the historical and archaeological information with respect to these skeletons, in combination with the above-mentioned research results, led to the conclusion that the researched skeletons belonged to a sepulchral field below the foundations of the church, which was there before the abbey church was built. This sepulchral field forms part of the settlement known from historical and archaeological information and for the greater part dates back to the 9th to 11th centuries, with a few graves dating from the Merovingian period (early 7th century).